Estudio de factibilidad para la creación de un centro de capacitación de contabilidad y auditoría en el cantón La Maná provincia de Cotopaxi - Villafuerte Toala, Ignacio Javier (2016)
The development of this research proposal is to provide quality accounting training service to citizens of Canton La Mana, as it has the support of professionals trained academically with appropriate scientific and technical knowledge, with high ethical and moral spirit trained at the Technical University of Cotopaxi La Mana, which is one of the strengths that allow the creation of the Training Center Accounting and Auditing whose mission is to provide accounting tax services to individuals and corporations, required and not required to keep accounting according to current regulations in the country; the creation of a training center, is to support directly the commercial sector in La Mana, especially with training on issues of tax and internal control, considering that a large part of the population it is dedicated to trade and also to agricultural production of a veriety of products, creating the emerging of small enterprises….